Influence of NOD2 Variants on Trichuris suis ova Treatment Outcome in Crohn's Disease - Simon U. Jaeger; Simon U. Jaeger; Elke Schaeffeler; Elke Schaeffeler; Stefan Winter; Stefan Winter; Roman Tremmel; Roman Tremmel; Jürgen Schölmerich; Nisar Malek; Eduard F. Stange; Matthias Schwab; et al. (Frontiers Media S.A., 2018)
A recent randomized study of whipworm Trichuris suis ova (TSO) in ileal Crohn's disease failed to demonstrate a clinical benefit compared to placebo after 12 weeks. Nonetheless, it has recently been shown that the spontaneous small intestinal inflammatory changes in Nod2-/- (Nucleotide-binding oligomerization domain 2) mice could be substantially ameliorated when these mice were colonized by Trichuris muris. Those and complementary epidemiologic findings in humans lead to the hypothesis that helminths may be advantageous only in patients carrying defective NOD2 variants. Thus, 207 participants of the TSO trial were retrospectively genotyped for six functional NOD2 genetic variants to evaluate whether the treatment outcome differed in patients carrying NOD2 variants. We observed no significant association of the NOD2 variants or their haplotypes with clinical outcome after TSO treatment.